Pengaruh Model Paired Storytelling dengan Menggunakan Media Wayang Kartun terhadap Keaktifan Siswa - Dita Astriani; Rajji K Adiredja; Dea Asri Pujiasti; De Budi Irwan Taofik (Institut Pendidikan Indonesia, 2023)
Indonesian language learning at one of the elementary schools in Garut Regency has not been able to accommodate students to be active in telling stories. Thus, we need a media that is able to stimulate student activity, one of which is the wayang cartoon media. This type of research uses experimental methods, with instruments in the form of questionnaires and observations. The subjects in this study were 25 grade 5 elementary school students. The result of the calculation of the t test is tcount of 23.10 and the value of ttable with a significant level of 0.173 α = 0.05 obtained ttable 0.173. From this analysis it was obtained that tcount = 23.10> ttable 0.173. Thus, there is a significant influence of the paired storytelling model and wayang cartoon media on student activity.